O efeito da poluição atmosférica na variabilidade da frequência cardíaca em indivíduos com excesso de peso - Base, Luis Henrique [UNIFESP] (2019)
Introduction. Among the several factors related to the development of cardiovascular diseases, air pollution and obesity contribute significantly to this increase. Objective. To analyze the effect of air pollution on the autonomic modulation of heart rate in overweight individuals. Method. We analyzed adult individuals, aged between 18 and 49 years, with BMI >25 kg/m2. The municipality of Cubatão (SP) was selected as an experimental area, due to a study carried out by the Companhia de Tecnologia de Saneamento Ambiental in 2001 and 2013, which proved toxic sources in the territory. It is a control area located in the municipality of Peruíbe (SP). Intergroup analyzes were performed with the linear indexes of the time and frequency domain, in addition to the geometric indexes. Result. There was a reduction in the general heart rate variability in the overweight individuals exposed to air pollution through SDNN, SD2, RRTri and TINN indexes (p = 0.012, p = 0.013, p-0.009, p = 0.010, respectively). In addition, the indexes responsible for parasympathetic control such as rMSSD, pNN50 and SD1 showed a tendency to fall in their values, as well as, the LF index, which represents the action of the sympathetic, although not significant. Conclusion. The study showed that overweight individuals exposed to air pollution had lower overall HRV when compared to the control group. In addition, parasympathetic and sympathetic modulation were shown to have a downward trend, although not significant.